Stripe pattern differences can be used to distinguish individual adult zebrafish. - Shinichi Meguro; Takahiro Hasumura (PLoS ONE)
Adult zebrafish are commonly used as disease models in biomedical research, but unlike in other model organisms such as rodents, there is no simple method for distinguishing individuals, even though the importance of individual differences is recognized in such research. We developed a side viewing device that can be used to capture images of stripe patterns and identified eight distinct components of stripe patterns on the caudal and anal fins that allowed us to distinguish individual fish. We found that the stripe patterns were consistent for at least 8 weeks in males and females of two lines of wild-type zebrafish. These results suggest that individual adult zebrafish can be distinguished in an easy and non-invasive manner, allowing researchers to incorporate individual differences in biomedical research as in rodent models.